Multilingualism and Cultural Diversity among Young People in Tetovo - Skenderi, Lindita (Acta Universitatis Danubius. Communicatio, 2024)
The relevance of educational reforms for the quality learning of foreign languages in higher education in the Balkan countries, where multilingualism and diversity are increasingly present in classrooms, is also the purpose of this research, which analyzes the impact of multilingualism on cultural diversity in the teaching of foreign languages. Having this objective, the research was carried out with 250 students from different ethnicities who attended foreign language classes. The questionnaire was composed of the main pedagogical and methodical educational components and indicators for foreign language teaching in higher education in the Republic of North Macedonia. Based on that, the questionnaire data indicate the level of acceptance of cultural diversity in learning a foreign language based on the perception that in this educational environment multilingualism is set as a standard. The results of the research indicate that multilingualism is the main bridge for getting to know cultural diversity, but still, as a psycho-social concept, it is not the main motive for easier learning of a foreign language among students.